2015
DOI: 10.1002/anie.201506186
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Handedness of Twisted Lamellae in Banded Spherulites of Isotactic Poly(2‐vinylpyridine) as Induced by Chiral Dopants

Abstract: Herein, we suggest a unique approach to control the handedness of twisted lamellae in banded spherulites of a stereoregular polymer, isotactic poly(2-vinylpyridine) (iP2VP). When (R)- or (S)-hexahydromandelic acid (HMA), which can associate with iP2VP, was introduced as a chiral dopant, mirror-image CD spectra in the complex systems showed induced circular dichroism (ICD) of the iP2VP by chiral HMA. Banded spherulites resulting from lamellar twisting due to the imbalanced stresses at the opposite folding surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
(24 reference statements)
0
36
0
Order By: Relevance
“…For example, when (R)-or (S)hexahydromandelic acid (HMA), which can associate with isotactic poly(2-vinylpyridine) (iP2VP), was introduced as a chiral dopant, mirror-image CD spectra in the complex systems were observed. [34] Moreover, a preferential sense of the twisted crystalline lamellae was also obtained in the iP2VP/HMA complex, thus suggesting the homochirality evolution from conformational to hierarchical chirality. The handedness of twisted lamellae in banded spherulites could be controlled by the chiral dopants.…”
Section: Crystallization With the Participation Of Chiralitymentioning
confidence: 89%
“…For example, when (R)-or (S)hexahydromandelic acid (HMA), which can associate with isotactic poly(2-vinylpyridine) (iP2VP), was introduced as a chiral dopant, mirror-image CD spectra in the complex systems were observed. [34] Moreover, a preferential sense of the twisted crystalline lamellae was also obtained in the iP2VP/HMA complex, thus suggesting the homochirality evolution from conformational to hierarchical chirality. The handedness of twisted lamellae in banded spherulites could be controlled by the chiral dopants.…”
Section: Crystallization With the Participation Of Chiralitymentioning
confidence: 89%
“…This also stands for PCL [75][76][77][78]. Recently, Ho et al [79] reported that chiral dopants can tune the twisting chirality of lamellar crystals of nonchiral isotactic poly(2-vinylpyridine), where (R)-and (S)-hexahydromandelic acid dopant induced right-handed and left-handed lamellar twisting, respectively.…”
Section: Factors Affecting Band Spacingmentioning
confidence: 99%
“…The mirror imaging of the CD spectra suggests the formation of right-and left-handed helical chains of the achiral polymer through complexation with the chiral guest [43]. Poly(phenylacetylene)s (PPAs) have also shown to present distinct chiroptical responses associated with their helicity.…”
Section: Induced Chiralitymentioning
confidence: 99%
“…The helical sense depends exclusively on the chiral monomer/donor cosolvent ratio, and this allows a flexible and controlled on/off tuning of the helicity of the copolymer. The mirror imaging of the CD spectra suggests the formation of right-and left-handed helical chains of the achiral polymer through complexation with the chiral guest [43]. Poly(phenylacetylene)s (PPAs) have also shown to present distinct chiroptical responses associated with their helicity.…”
Section: Induced Chiralitymentioning
confidence: 99%